Film fabularny jako narzędzie kuratora i badacza sztuki - Ronduda, Łukasz (Artium Quaestiones, 2020)
In the essay, the author, Łukasz Ronduda, relates his own work as an artist, a film director, an art historian and curator, discussed in the light of the cinematic turn and the formation of common ground between cinema and contemporary art in both artistic and institutional sense. Ronduda looks closely at his two full-length feature films: Performer (2015) and Serce miłości (Heart of Love) (2017) and highlights their wider context. The first frame of reference spans from experimental films to contemporary full-length productions dedicated to wide audience. The second reference is his own work involving academic research, curating, writing a novel and the creation of a found footage film. In this self-presentation, Ronduda discloses his different attempts to find the right medium to speak about and analyze contemporary art. The full-length film turned out to be particularly effective medium in its ability to express the truth by means of fiction, placing him between creation and institutional structure. Film as a medium of interpreting art seems to productively question fixed boundaries between research, criticism and art.